Idiopathic intracranial hypertension in a patient with a history of migraine: a case report - Gonçalves, Christian; Kuhn, Leonardo josé; Lazari, Alan Henrique de; Oliveira, Sara Pessoa de; Barboza, Bárbara Evelin Gonçalves (Headache Medicine, 2024)
IntroductionIdiopathic intracranial hypertension (IIH) is marked by elevated intracranial pressure without a known cause, often affecting women of childbearing age and linked to obesity. Diagnosing IIH can be tricky, especially in patients with chronic headaches like migraines. This report discusses a case of IIH in a long-term migraine sufferer, stressing the importance of early detection and effective treatment.Case ReportA 44-year-old woman with migraines since menarche sought medical help in August 2021 due to more frequent and intense headaches, occurring three times a week with light and sound sensitivity and nausea. An MRI in September 2021 showed rare anomalies. Initially treated with topiramate and nortriptyline, her headaches decreased to twice a month by May 2022. However, in November 2022, an ophthalmologist found bilateral papilledema, and she reported retroocular pain and transient visual obscurations. A lumbar puncture confirmed IIH with an opening pressure of 32.5 cmH2O, and she was prescribed acetazolamide. Despite some headache relief, she experienced nausea and visual distortions. Adjustments in her medication and a five-kilogram weight loss improved her symptoms, though issues in the left eye's visual field persisted.CommentThis case highlights the challenges of managing IIH in migraine patients. New headache patterns and visual symptoms were key to suspecting IIH, confirmed by lumbar puncture. Acetazolamide effectively reduced her intracranial pressure, while nortriptyline helped manage sleep issues. Weight loss significantly improved symptoms, emphasizing the need for a multidisciplinary approach between neurologists and ophthalmologists are for optimal care.